Redux Sellow: revealing Sellow's collections from the Herbier Impérial du Brésil at the Paris Herbarium - de Moraes, Pedro Luís Rodrigues [UNESP] (Magnolia Press, 2023)
This research aimed to locate and list all specimens belonging to the so-called Herbier Impérial du Brésil (HIB: Imperial Herbarium of Brazil), in the Muséum National d'Histoire Naturelle (P) in Paris. In 1833, Charles Gaudichaud-Beaupré removed this collection from what was then the Imperial and National Museum of Rio de Janeiro, currently the National Museum of Rio de Janeiro (R). Since then, these specimens have been labelled as HIB plus a collection number, with one of four “Provinces” designated as “Mato Grosso”, “Minas Gerais”, “Rio Grande”, “São Paulo” and “C. Gaudichaud 1833”. For this reason, most specimens have erroneously been attributed, both in the literature and database at P (Sonnerat), to collection by Gaudichaud-Beaupré. I located these specimens through virtual searches in the Sonnerat database and two in-person visits to P. As a result, 3,441 specimens were located, but there should be another 262 specimens that are part of the sequential numbering for each “Province”. The specimens located belong to 147 APG IV families, 786 genera, 1,916 species of phanerogams and 14 families, 34 genera, 53 species of cryptogams. Of relevance is that ca. 555 of these specimens are nomenclatural types and another ca. 980 specimens are likely duplicates of types described from Sellow's collections. Except for specimens from Mato Grosso, where Sellow never collected, evidence that he is the collector of specimens from other provinces comes from 812 specimens that still have his original labels tied to the branches or traces of destroyed labels. Many specimens without Sellow's original labels belong to species described from his collections in Berlin and, in several cases, were only known at the time from them, including morphological and phenological data. In view of this, some cases are exemplified and detailed in which specific names have nomenclatural priority, but which have been neglected, or remained doubtful, and could be resolved from HIB specimens, by being directly and/or indirectly related to well-documented specimens. It was also possible to resolve or improve the localities and collection periods of many of these specimens, especially those with the original labels, without the laconic “Brasilia” and/or “Montevideo” traditionally associated with the “Sellow s.n.” collections. Still incipiently, information is also presented on the collections (HIB duplicates) in the herbarium of the National Museum of Rio de Janeiro (R), for which collection data are partially digitised (≈ 14%). Finally, it should be noted that this research is a first step towards a more comprehensive study, in which ideally a compilation of all Sellow collections, spread across the four corners of the globe, would be accomplished, enabling a better understanding and resolution of taxonomic and/or nomenclatural issues that still remain untouched or unresolved. Sellow's collection is, perhaps, the most important of those collected in 19th century Brazil, which has not been given serious consideration. The HIB collections shed light on old and new taxonomic issues, circumscription, geographical distribution and typification, to list only some of the related aspects which will improve knowledge of the primary source of information on our botanical heritage, that is, our flora. As an example, a lectotype is designated for the name Chrysocoma megapotamica Spreng., which has nomenclatural priority over the heterotypic synonym Eupatorium ericoides DC., the basionym of Disynaphia ericoides (DC.) R.M.King & H.Rob., the latter wrongly taken as the correct name of this taxon. Therefore, I here propose a nomenclatural combination for this name in Disynaphia.
Keywords: Friedrich Sellow; historical collections; National Museum of Rio de Janeiro; nomenclature of Brazilian plants; taxonomy of Brazilian plants; typification of Brazilian plants